The effect of thriving at work on work-family conflict: the mediating role of workaholism - Ni, Xudong; Zeng, Zining; Zhou, Jinyu (Frontiers in Psychology, 2023)
In this study, based on resource conservation theory, we studied the effect of thriving at work on work-family conflict, the mediating effects of workaholism, and the moderating effects of work-family separation preference and trust climate. By analyzing 372 samples, we found that thriving at work was significantly and positively related to work-family conflict; workaholism partially mediated the relationship between thriving at work and work-family conflict; work-family separation preference negatively moderated the relationship between thriving at work and workaholism. The moderating role of the trust climate was not verified.